2015
DOI: 10.1186/s13104-015-1184-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori in dyspeptic patients at a tertiary hospital in a low resource setting

Abstract: BackgroundMore than half of the world’s population is infected with Helicobacter pylori (H. pylori), the primary cause of chronic gastritis. Chronic gastritis is associated with peptic ulcer and in advanced stages with an increased risk of developing gastric adenocarcinoma. In many developing countries access to upper gastrointestinal (UGI) endoscopy services is limited. As a result, many UGI diseases are treated empirically.ObjectiveTo determine the prevalence of H. pylori in patients presenting with dyspepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 13 publications
3
31
2
2
Order By: Relevance
“…Because of this, many patients with PUD are treated empirically Table 3 Hazard ratios and 95% confidence intervals of peptic ulcer diseases associated with cumulative defined daily dose of statins. [33]. In the last decade though, the causes of PUD have changed from H. pylori to NSAIDs or idiopathic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, many patients with PUD are treated empirically Table 3 Hazard ratios and 95% confidence intervals of peptic ulcer diseases associated with cumulative defined daily dose of statins. [33]. In the last decade though, the causes of PUD have changed from H. pylori to NSAIDs or idiopathic ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of Shmuely et al in Nakuru (Kenya), which obtained a frequency of 71% in 2013 [13]. Werme et al Obtained only 36% in Kampala (Uganda) the same year but related the weakness of this frequency to longer duration of their study [15].…”
Section: Discussionmentioning
confidence: 88%
“…While Obayo et al, (2015) H. pylori was diagnosed in 75.6% among the biopsied patients. Oling et al, 2015 found the prevalence of H. pylori gastritis was 36%. In China the mean prevalence of H. pylori infection in the endoscopy-referral patient population was 31.97 %, and it mirrored a marked significant linear decline trend from 42.40 % in 2003to 23.82 % in 2012as reported by Jianget al, 2016.Ansari et al, 2016 found the overall prevalence of colonization of H. pylori was found as less as to be 16%.…”
Section: General Populationmentioning
confidence: 91%
“…The incidence of H. pylori infection in Ghana may be lower than previously reported due to changing socioeconomic factors, increased PPI and antibiotic useAdu-Aryeeet al, 2016). The burden of H. pylori infection among dyspeptic patients was high which decrease after antibiotic empirical treatment (Oling et al, 2015).…”
Section: Antibiotic Sensitivity To H Pylori Growthmentioning
confidence: 98%
See 1 more Smart Citation